Environmental Technical Efficiency Measurement of Processing Industry in East Java in 2006-2009 - Septiriana, Ratih Twi; Kusumawardani, Deni (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2016)
CO2 emission is the greatest source of global warming that pose serious threats on environment, ecology, and socio-economic system. In the production process, CO2 is considered as undesirable output that always rises as long as desirable output is produced. Indonesia, as the one of the biggest emitters of CO2 emission, has been committing in reducing emission up to 26 percent for 2020. Using panel data, stochastic frontier analysis (SFA) utilized to evaluate the environmental technical efficiency of manufacturing industry in Java on 2006-2009. The trans-log hyperbolic distance function has been chosen since this model can accommodate environmental characteristic of production technology. The empirical result shows the average environmental technical efficiency is 0,834. This study also investigates the factors that explain the level of environmental technical efficiency of firm. The results reveal that there are seven factors that significantly affect environmental technical efficiency namely: firm size, ownership status and foreign investment, type of industry, composition effect, scale effect, and technical effect. The finding of this paper indicates that environmental technical efficiency among manufacturing industry in Java still can be improved by focusing on those seven factors.